Klonální analýza populace meningokoků z invazivního onemocnění a od zdravých nosičů izolovaných v České republice v období 1971--2014 (květen) - Jandová, Z; Musílek, M; Vacková, Z; Kozáková, J; Křížová, P (Epidemiologie, mikrobiologie, imunologie, 2015)
OBJECTIVE: To present the results of clonal analysis of the meningococcal populations isolated from invasive disease and healthy carriers in the Czech Republic over four decades. MATERIAL AND METHODS: A total of 2179 isolates of Neisseria meningitidis from 1971-2014 (May) were studied: 1093 isolates from patients with invasive meningococcal disease (IMD) and 1086 isolates from healthy carriers. All study isolates were analysed by multilocus sequence typing (MLST), one of the major methods used in molecular epidemiology of IMD. RESULTS: More than 94 % of N. meningitidis isolates from IMD were assigned to serogroups B or C. The strains of the leading serogroup B were genetically highly heterogeneous: 1093 isolates were assigned to 25 clonal complexes. Similarly, the strains of the second leading serogroup C appeared genetically heterogeneous and were classified into 19 clonal complexes. The third leading serogroup Y of IMD isolates showed an opposite tendency and appeared highly homogeneous, with only three clonal complexes being detected. Over 75% of the predominant clonal complexes of IMD isolates of both serogroup Y (cc23) and serogroup C (cc11) were classified as hypervirulent and, as such, posed the highest risk to the host population. Over 80% of IMD isolates of serogroup B were assigned to hypervirulent clonal complexes (cc32, cc41/44, cc18, cc269, and cc11). Of 1086 N. meningitidis isolates from healthy carriers, 41.4% were non-serogroupable, i.e. designated N. meningitidis NG. Classification of these isolates into clonal complexes was highly heterogeneous. In total, 28 clonal complexes were identified of which only a minority were hypervirulent. CONCLUSIONS: The analysis of MLST data on strains collected over four decades revealed that the population of N. meningitidis strains involved in IMD differ genetically from N. meningitidis strains isolated from healthy carriers. These results are relevant to both the optimal use of preventive measures in a focus of IMD and to the development of an effective meningococcal vaccine and vaccination strategy guidelines.
Keywords: Meningococcal Infections; Česká republika; Middle Aged; Carrier State; mužské pohlaví; Adult; Czech Republic; antigeny bakteriální; Neisseria meningitidis; Antigens, Bacterial; Multilocus Sequence Typing; ženské pohlaví; meningokokové infekce; Humans; lidé středního věku; dospělí; přenašečství; multilokusová sekvenční typizace; Female; Neisseria meningitides - multilocus sequence typing - clonal analyse.; lidé; Male